Histone Deacetylase (HDAC) Inhibition Induces IκB Kinase (IKK)-dependent Interleukin-8/CXCL8 Expression in Ovarian Cancer Cells - Gatla, Himavanth R. (J Biol Chem, 2017)
Overexpression of the pro-angiogenic chemokine IL-8 (CXCL8) is associated with a poor prognosis in several solid tumors, including epithelial ovarian cancer (EOC). Even though histone deacetylase (HDAC) inhibition has shown remarkable antitumor activity in hematological malignancies, it has been less effective in solid tumors, including EOC. Here we report results that may explain the decreased efficiency of HDAC inhibition in EOC, based on our data demonstrating that HDAC inhibition specifically induces expression of IL-8/CXCL8 in SKOV3, CAOV3, and OVCAR3 cells. Suppression or neutralization of vorinostat-induced IL-8/CXCL8 potentiates the vorinostat inhibitory effect on cell viability and proliferation. The IL-8/CXCL8 expression induced by vorinostat in EOC cells is dependent on IκB kinase (IKK) activity and associated with a gene-specific recruitment of IKKβ and IKK-dependent recruitment of p65 NFκB to the IL-8/CXCL8 promoter. In addition, HDAC inhibition induces acetylation of p65 and histone H3 and their IL-8/CXCL8 promoter occupancy. In vivo results demonstrate that combining vorinostat and the IKK inhibitor Bay 117085 significantly reduces tumor growth in nude mice compared with control untreated mice or either drug alone. Mice in the combination group had the lowest IL-8/CXCL8 tumor levels and the lowest tumor expression of the murine neutrophil [7/4] antigen, indicating reduced neutrophil infiltration. Together, our results demonstrate that HDAC inhibition specifically induces IL-8/CXCL8 expression in EOC cells and that the mechanism involves IKK, suggesting that using IKK inhibitors may increase the effectiveness of HDAC inhibitors when treating ovarian cancer and other solid tumors characterized by increased IL-8/CXCL8 expression.